Identification of differentially expressed miRNAs in human cells infected with different Zika virus strains - Machado, Francielly Cristina [UNESP]; Bittar, Cíntia [UNESP]; Rahal, Paula [UNESP]; Calmon, Marilia Freitas [UNESP] (Springer Nature, 2021)
Infection with distinct Zika virus (ZIKV) strains in in vitro and in vivo models has demonstrated that the host’s response to infection is strain-dependent. There has been no analysis of the impact of infection with different ZIKV strains on miRNA expression in human cells. We investigated miRNA expression in PNT1A cells upon infection with an African ZIKV strain (MR766) and a Brazilian ZIKV strain (ZIKVBR) using PCR array. Sixteen miRNAs were modulated in PNT1A cells: six miRNAs were modulated by both strains, while a set of ten miRNAs were modulated exclusively by ZIKVBR infection. In silico analysis showed that nine significant KEGG pathways and eight significant GO terms were predicted to be enriched upon ZIKVBR infection, and these pathways were related to cancer, environmental information processing, metabolism, and extracellular matrix. Differential modulation of miRNA expression suggests that distinct strains of ZIKV can differentially modulate the host response through the action of miRNAs.